2016
DOI: 10.1038/jhh.2016.67
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium body burden and increased blood pressure in middle-aged American Indians: the Strong Heart Study

Abstract: Cadmium is an environmental pollutant that has been associated with cardiovascular disease in populations, but the relationship of cadmium with hypertension has been inconsistent. We studied the association between urinary cadmium concentrations, a measure of total body burden, and blood pressure in American Indians, a U.S. population with above national average cadmium burden. Urinary cadmium (Cd) was measured using inductively coupled plasma mass spectrometry, and adjusted for urinary creatinine concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…The associations were similar in most study subgroups, including never-smokers. Urinary cadmium concentrations were also associated with an increased risk for incident peripheral arterial disease in models adjusted for smoking [22], and elevated systolic blood pressure in models adjusted for kidney function [23]. Also in the Strong Heart Study, Garcia-Esquinas et al [24] reported significant associations between urinary cadmium concentrations and total incidence of cancer, as well as increased mortality from lung cancer, pancreatic cancer, and all smoking-related cancers combined.…”
Section: Resultsmentioning
confidence: 99%
“…The associations were similar in most study subgroups, including never-smokers. Urinary cadmium concentrations were also associated with an increased risk for incident peripheral arterial disease in models adjusted for smoking [22], and elevated systolic blood pressure in models adjusted for kidney function [23]. Also in the Strong Heart Study, Garcia-Esquinas et al [24] reported significant associations between urinary cadmium concentrations and total incidence of cancer, as well as increased mortality from lung cancer, pancreatic cancer, and all smoking-related cancers combined.…”
Section: Resultsmentioning
confidence: 99%
“…Increased risk of hypertension by Cd exposure has been reported for the Korean population (Lee and Kim 2012;Lee et al 2016), Chinese population in an area with Cd contamination ) and the U.S. population (Scinicariello et al 2011;Franceschini et al 2016). The U.S. population studies show that blood Cd level as low as 0.4 µg/L is associated with an increased risk of hypertension in Caucasian women (OR 1.54, 95% CI 1.08-2.19) and in Mexican-American women (OR 2.38, 95% CI 1.28-4.40) and that the prevalence of hypertension in Black, Caucasian and Mexican-American women (men) in the U.S. NHANES 1999-2006 was 40.7 (30.1), 32.2 (36.2) and 19.4 (16.7) %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific gravity correction of urinary Cd concentrations has been used in multivariate analysis to evaluate effects of Cd exposure on blood pressure. In the Strong Heart Study (Franceschini et al 2016), higher urinary Cd levels were associated with higher systolic blood pressure among American Indian participants (n = 3,714, mean age 56 yrs), after adjustment for age, sex, geographic area, body mass index, smoking and kidney function. Of note, effects of Cd exposure on hypertension risk, seen in American Indians, were independent of smoking exposure.…”
Section: Cadmium and Hypertensionmentioning
confidence: 99%
“…They reported an independent association between high cadmium levels and intima–media thickness, exceeding the 90th percentile in distribution, representing early atherosclerotic vessel wall thickening [49]. Cadmium has also been found to raise blood pressure, an established risk factor for cardiovascular disease [50,51]. In a large population study of NHANES III participants between 1988 and 1994, creatinine-corrected urinary cadmium levels in men were associated with an increase in risk of all-cause and cardiovascular mortality, including coronary artery disease-associated mortality [52].…”
Section: Toxic Metals and Vascular Disease Mechanisms And Evidencementioning
confidence: 99%